ISOLASI DAN KARAKTERISASI SENYAWASENYAWA PEMANIS DARI DAUN SAGA MANIS ( ABRUS PRECATORIUS L.) - Siti Isnijah S.P.; Sri Hartati; Leonardus B.S.Kardono (Jurnal Kimia Terapan Indonesia, 1993)
The sweet principles of A.precatorius leaves had been claimed as glycyrrihizin compound. The recent publication however showed that A. precatorius leaves, plant materials collected in Miami (Florida-USA), do not contain glycyrrhizin. The sweet tasting compound are triterpene cycloortan« glycosides, i.e : abrusoside A.B,C and D, having sweetness potencies in the range 30-100 times greater than sucrose. Compare to theA.precalorius leaves from Miami (Florida - USA), the glycosides of A. precatorius leaves collected in Bandung, (Indonesia), showed different thin layer chromatographic performance. By using techniques of bioactivity guided fractionation, some sweet compounds in A.precatorius leaves from Bandung could be isolated and characteriud. These compounds may be potential for sugar substitution for the diet of diabetic and obesitic patients.